Optical coherence tomography for retinal imaging in multiple sclerosis - Zimmermann, Hanna (Degener Neurol Neuromuscul Dis, 2014)
Visual disturbances caused by inflammatory and demyelinating processes of the visual system, mainly in the optic nerve, are a common symptom in multiple sclerosis (MS). Optical coherence tomography (OCT) is a tool that is increasingly used for quantifying retinal damage in MS and other neurologic diseases. Based on spectral interferometry, it uses low-coherent infrared light to generate high-resolution spatial images of the retina. The retinal nerve fiber layer (RNFL) consists of unmyelinated axons that form the optic nerve, and thus represents a part of the central nervous system. OCT allows for noninvasive measurements of RNFL thickness in micrometer resolution. With the help of OCT, researchers have managed to demonstrate that eyes of MS patients show distinct RNFL thinning after an event of acute optic neuritis in MS, and even subclinical damage in eyes with no previous optic neuritis. OCT is also a useful tool in terms of providing a differential diagnosis of MS toward, for example, neuromyelitis optica, a disease that usually shows stronger retinal thinning, or Susac syndrome, which is characterized by distinct patchy thinning of the inner retinal layers. RNFL thinning is associated with magnetic resonance imaging-derived measurements of the brain, such as whole-brain atrophy, gray and white matter atrophy, and optic radiation damage. These features suggest that OCT-derived retinal measurements are a complement for measuring central nervous system neurodegeneration in the context of clinical trials – for example, with neuroprotective substances.